2019
DOI: 10.1002/adfm.201907066
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Based Functional Nanoplatforms: Nanosynthetic Construction, Physiochemical Property, and Theranostic Applicability

Abstract: Transition metal‐based nanoparticles have shown their broad applications in versatile biomedical applications. Although traditional iron‐based nanoparticles have been extensively explored in biomedicine, transition metal manganese (Mn)‐based nanoparticulate systems have emerged as a multifunctional nanoplatform with their intrinsic physiochemical property and biological effect for satisfying the strict biomedical requirements. This comprehensive review focuses on recent progress of Mn‐based functional nanoplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 256 publications
1
73
0
Order By: Relevance
“…exploited nanomaterials in theranostic nanomedicine, among which a myriad of iron (Fe)-involved and manganese (Mn)composed nanosystems exert the specific function in disease treatment based on their magnetic/paramagnetic property, intrinsic microenvironment-responsive behavior, and high biocompatibility, as reflected by thousands of publications regarding these two transitional metal element-based biomaterial nanosystems. [30][31][32][33][34][35] Alternatively, copper ions (Cu 2+ ) are the bioactive components with the specific capability for promoting angiogenesis, which is originated from their performance on stabilizing the expression of hypoxia-inducible factor (HIF-1 ) and secretion of vascular endothelial growth factor (VEGF), further enhancing the recruitment and differentiation of cells during the blood vessel-producing procedure. [36][37][38][39][40][41][42] It has been fully revealed that Cu ions can facilitate the cell migration, angiogenesis, and collagen deposition for the specific biomedical implementation on accelerating wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exploited nanomaterials in theranostic nanomedicine, among which a myriad of iron (Fe)-involved and manganese (Mn)composed nanosystems exert the specific function in disease treatment based on their magnetic/paramagnetic property, intrinsic microenvironment-responsive behavior, and high biocompatibility, as reflected by thousands of publications regarding these two transitional metal element-based biomaterial nanosystems. [30][31][32][33][34][35] Alternatively, copper ions (Cu 2+ ) are the bioactive components with the specific capability for promoting angiogenesis, which is originated from their performance on stabilizing the expression of hypoxia-inducible factor (HIF-1 ) and secretion of vascular endothelial growth factor (VEGF), further enhancing the recruitment and differentiation of cells during the blood vessel-producing procedure. [36][37][38][39][40][41][42] It has been fully revealed that Cu ions can facilitate the cell migration, angiogenesis, and collagen deposition for the specific biomedical implementation on accelerating wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26–29 ] Transitional metal element‐involved nanosystems are one of the most representative and exploited nanomaterials in theranostic nanomedicine, among which a myriad of iron (Fe)‐involved and manganese (Mn)‐composed nanosystems exert the specific function in disease treatment based on their magnetic/paramagnetic property, intrinsic microenvironment‐responsive behavior, and high biocompatibility, as reflected by thousands of publications regarding these two transitional metal element‐based biomaterial nanosystems. [ 30–35 ]…”
Section: Introductionmentioning
confidence: 99%
“…Tri-therapeutic strategies have successfully eliminated tumors both in vitro and in vivo (Curcio et al, 2019 ). Similarly, other MNPs, including Mo, Pd, Pt, Mn, and Bi nanoparticles, have been extensively investigated as excellent phototherapy and imaging agents, which can be used in clinical studies based on their biocompatible behaviors (Badrigilan et al, 2020 ; Guo et al, 2020b ; Jiang et al, 2020 ; Qian et al, 2020 ).…”
Section: Application Of Stimuli-triggered Metallic Nanotherapeutics Imentioning
confidence: 99%
“…Manganese-based nanomaterials can release manganese ions to catalyze Fenton-like reactions, making them widely used in cancer diagnostics and therapeutics [ 96 98 ]. Owing to the enhanced spin–spin relaxation of manganese, manganese-based nanomaterials also exhibit low toxicity, tumor targeting ability, and potential magnetic resonance (MR) imaging contrast [ 99 ].…”
Section: Introductionmentioning
confidence: 99%